Kearifan Lokal Dalam Konservasi Sumber Mata Air Pada Situs Arkeologi di Kabupaten Dompu - Nyoman Rema; Nyoman Arisanti; Satrio Satrio (PURBAWIDYA: Jurnal Penelitian dan Pengembangan Arkeologi, 2023)
The presence of spring in Dompu Regency is an asset for the sustainability of natural resources and cultural resources in the surrounding area. This study aims to determine the conservation efforts of springs in the Dompu site area based on local wisdom and its current impact. This research utilizes ecological, isotope, and hydrochemical approaches. Data was collected through field observations and water sampling at the Riwo Spring. The data were analyzed using ecological, isotope, and hydrochemical approaches to samples of water followed by qualitative descriptive analysis. Based on the results of isotope and hydrochemical studies on the Riwo spring, it showed that the spring has good water quality, which means it is still suitable for consumption and this spring is young, so the balance of the surrounding environment is very important to maintain. The sustainability of springs is sought by applying local wisdom, one of which is leka dana. Leka dana can be used to determine policies for environmental conservation policy, conservation of forest catchment areas, and sustainable springs in Dompu Regency. Based on the results of the isotope and hydrochemical study result, it is recommended that in Riwo Spring areas and the surrounding forest, which served as recharge areas, should not be cleared for plantations or settlements. These recharge areas should be preserved and if necessary reforested. Keywords: spring conservation, archeology, natural isotopes, hydrochemistry, local wisdom